(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics and related factors of patients with horizontal forehead lines at the National Hospital of Dermatology and Venereology. Subjects and Methods: A prospective cross-sectional descriptive study was conducted on 223 patients with horizontal forehead wrinkles who attended the hospital from August 2024 to August 2025. Results: The mean age of the study population was 34,5 ± 8,6 years, with females accounting for 76,2%. The highest prevalence of forehead wrinkles was observed in the 30–<50 years age group (60,1%). Regarding treatment, the use of topical creams was most common (56,5%), followed by no intervention (18,8%), while invasive procedures were less frequent. Type I wrinkle pattern predominated (88,3%), and wrinkles extending across the entire forehead width were the most frequent location (88,6%). Dynamic wrinkles were mainly of moderate severity, whereas static wrinkles were mostly mild or minimal. FLGS scores for both dynamic and static wrinkles increased with the frequency of habitual frowning. Static wrinkle severity was lower among participants using sunscreen and increased with age, with those aged ≥50 years having higher FLGS scores than younger groups. Conclusion: Horizontal forehead wrinkles primarily occurred in the 30–<50 years age group. Type I pattern and wrinkles across the full forehead width were predominant. Dynamic wrinkle severity was associated with habitual frowning, while static wrinkle severity was associated with habitual frowning, sunscreen use, and age.